(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Rapid urbanization, exhausted resources, imbalance in urban hydrological cycle, greatpressure on ecological functions, unhygienic and unhealthy environment is the outline in almost allIndian cities. Tremendous pressure on land caused by increasing urban population has led to asignificant increase in impermeable and paved surfaces which has reduced the infiltration rate. Undernatural climatic parameters, water acts as a complete cycle of precipitation, evaporation, surface waterrunoff and infiltration. However, in cities this cycle is disrupted. Urban water is polluted and unable topercolate into the ground due to its paved surfaces, which results in rapid collection and drainage intopublic sewers which do not get the time to evaporate. Ultimately, it has negative effects on groundwaterrecharge. Mismanagement of surface water and urban runoff results in flooding, erosion, and waterproblems. All these issues clearly indicate the need for efficient solutions for urban stormwatermanagement. This research aims to identify strategies that can potentially integrate water cycle loop,water supply, groundwater and storm water with effective spatial design considerations that are watersensitivein nature through a literature review. The research recommends techniques at urban designlevel and then individual design level towards building water-sensitive sustainable cities in considerationwith the Sustainable Development Goals 2030, that covers clean water, sanitation and sustainable cities,as well as community involvement, as significant priorities.